Seminari Tinggi Fermentum : Kebersatuan Calon Imam Ragam Budaya, Satu Silih Asih - Felix, Fransiskus; Viktorahadi, R.F. Bhanu (FOCUS, 2024)
This research discusses the cultural differences of each candidates of priest at Fermentum Major Seminary. Cultural differences are a challenge for efforts to unify the vision with the Fermentum Major Seminary formation program. By using the unifying elements offered by the RFIS document, the candidates of priest create unity among community members with an attitude of ‘Silih Asih’. ‘Silih Asih’ is a Sundanese philosophy that continues to be lived by the people of West Java. This research uses empirical research methods, observations, a logical thinking framework which is manifested in a sequence of narratives, descriptions and analysis. This method is complemented by literature study. Empirical research was carried out using short interviews to find out valid data from each members regarding their place of origin and ethnicity, pastoral care together with the congregation. As a result, good and correct processing is needed in dealing with these differences. The element of unity offered by the Church’s document Ratio Fundamentalis Institutionis Sacerdotalis (RFIS) and the Guidelines for the Formation of Candidates for Priests in the Bandung Diocese help the candidates of priest to find unity of vision with the seminary institution and the pastoral vision of the Bishop of Bandung. The development of an attitude of compassion must be carried out and lived by members at the Fermentum Major Seminary of the Bandung Diocese.